Resting heart rate and blood pressure: between women aerobic and bharathanatyam dancers. - Sabaananth, S.; Gopinath, V. (Mannar Thirumalai Naicker College,Madurai, 2012)
The purpose of this study was to compare resting heart rate and blood pressure between Aerobic and Bharathanatyam dancers. To achieve the purpose sixty (N=60) women dancers were selected from Jaffna, Sri Lanka, and they were classified in to Aerobic Dancers [(AD), (n=30, practice aerobic dance 90 to 120 min / day for 5 to 6 day / week over the period of minimum 5 years)] and Bharathanatyam Dancers[(BD)( n=30, practice bharathanatyam 90 to 120 min / day for 5 to 6 day / week over the period of minimum 5 years)] were selected as subjects, their mean age were 17 ± 1.3 years. They were measured resting heart rate using Palpating the radial artery for full one minute for each subject and blood pressure using Standardized sphygmomanometer and stethoscope. The resting heart rate and blood pressure were taken during early morning hours, the collected data were statistically treated by using independent‘t’ test , 0.05 level of confidence was fixed to test the significance. The result shows that Aerobic Dancers were lesser than Bharathanatyam Dancers on RHR, SBP, and DBP. Hence it was concluded that, aerobic dancers have lower RHR, SBP, and DBP
Keywords: RHR; SBP; DBP; Aerobic Dance; Bharathanatyam Dance